1967
DOI: 10.1139/v67-226
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of thiyl radicals. II. The photolysis of methyl disulfide vapor

Abstract: The photolysis of methyl disulfide vapor in the pressure range 2-25 Torr a t wavelengths between 2 300 and 2 800 and a t 2 288 A has been examined and the effect of temperature, pressure, added inert gases, ethyl disulfide, and nitric oxide determined.The primary process is a direct production of two CH3S radicals which have excess energy and which can be observed as methyl thionitrite when NO is present during the decomposition. When pure disulfide is photolyzed the inajor observable product is methanethiol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…However, until more information is available on the excitation possibilities in disulfide molecules, further speculation is unwarranted. There is, however, experimental evidence that an excited disulfide molecule is also important in the photolysis of pure disulfides (10).…”
Section: Natlrre Of the Prin~ary Process A~d Fates Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…However, until more information is available on the excitation possibilities in disulfide molecules, further speculation is unwarranted. There is, however, experimental evidence that an excited disulfide molecule is also important in the photolysis of pure disulfides (10).…”
Section: Natlrre Of the Prin~ary Process A~d Fates Of Thementioning
confidence: 99%
“…This is not too surprising since the formation of ethylene and hydrogen sulfide via reaction [10] requires a much more drastic rearrangement of the ethanethiol molecule than does simple C-S bond cleavage, and thus reaction [lo] might be expected to be somewhat Can. J. Chem.…”
Section: Natlrre Of the Prin~ary Process A~d Fates Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…In Part I1 of this series (5) it was shown that in the gas phase methyl disulfide photolyzes with S-S bond scission. The main fate of the CH,S radicals produced at substrate pressures between 2 and 25 Torr is recombination to reform the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The photolyses were conducted in a conventional high vacuum system described previously (3). The light source was a Hanovia 30620 medium pressure mercury lamp filtered to remove wavelengths less than 2000 A.…”
Section: Introductionmentioning
confidence: 99%